Distribusi Spasial Rajungan (Portunus pelagicus) pada Musim Timur di Perairan Pulau Lancang, Kepulauan Seribu - Syamsul Bahri Agus; Nimmi Zulbainarni; Adriani Sunuddin; Tarlan Subarno; Aditya Hikmat Nugraha; Insaniah Rahimah; Andi Alamsyah; Rosdyani Rachmi; . Jihad (Institut Pertanian Bogor, 2016)
A study was carried out to assess the present status of blue swimmer crab (Portunus pelagicus) in Lancang Island, incorporating identification of fishing ground, also measurement of environmental condition and crab biometry. Monthly catch assessment was performed on JuneSeptember 2015 at three landing bases using structured questionnaire and morphometric sampling of minimum randomly selected 30 crabs. Bathymetric survey was conducted to produce depth-contoured maps combined with certain oceanographic parameters (sea surface temperature, salinity, water clarity, total suspended solids, dissolved oxygen, and nitrate-NO3) measured at 15 sampling sites. A grid map was produced to identify key areas of crab fishing grounds, recruitment habitat, and spawning habitats. During southeast monsoon, main fishing ground was distributed in the western and southern part of Lancang Island (grid C3, C4, and D5). In general, crab yields were dominated by female (66.9%) and 43.8% of them were bearing eggs. Four size classes were determined from frequency distribution of carapace width (Class 1 = 7.0-10.6 cm; Class 2 = 10.7-14.2 cm; Class 3 = 14.3-17.8 cm; and Class 4 = 17.9-21.5 cm), with Class 2 as the most prominent catch. Referring to ontogenetic migration trait of the species, presumed recruitment habitat for blue swimmer crab in Lancang Island is located at A6, where abundant juveniles were harvested in the area with strong oceanic influence and depth range of 24-30 m. Spatial coherence on the distribution of bearing egg female with several environmental parameters (sea surface temperature, salinity, and dissolved oxygen) indicates strong estuarine influence is required for crab spawning habitat at C3 and